2016
DOI: 10.1016/j.heares.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Information theoretic evaluation of a noiseband-based cochlear implant simulator

Abstract: Noise-band vocoders are often used to simulate the signal processing algorithms used in cochlear implants (CIs), producing acoustic stimuli that may be presented to normal hearing (NH) subjects. Such evaluations may obviate the heterogeneity of CI user populations, achieving greater experimental control than when testing on CI subjects. However, it remains an open question whether advancements in algorithms developed on NH subjects using a simulator will necessarily improve performance in CI users. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Listening in noise is a clear challenge, which is not handled in the same way by CI users and NH people. Noise flattens the spectrum and the subsequent structures in the auditory system do not react identically [37]. The study of speech recognition in noise has become of great interest as it is present in daily listening conditions.…”
Section: Listening In Noisementioning
confidence: 99%
“…Listening in noise is a clear challenge, which is not handled in the same way by CI users and NH people. Noise flattens the spectrum and the subsequent structures in the auditory system do not react identically [37]. The study of speech recognition in noise has become of great interest as it is present in daily listening conditions.…”
Section: Listening In Noisementioning
confidence: 99%
“…Cochlear implants (CI) have successfully restored partial hearing to over 400,000 deaf persons in the world and the rhythm of implantations is high in the world with a minimal rate of about 30,000 implantations [1].…”
Section: Cochlear Implants and Agingmentioning
confidence: 99%
“…Then other settings on the strategy have their influence: sampling rate, filters settings, length of the time frame (window), and they have been studied by many authors [1,18,19,20]. Most of the studies concluded to an advantage of the CIS coding over n-of-m. Then, the Advanced Combination Encoder (ACE) scheme is very efficient; it uses a very fast updating of the data and therefore provides a fine temporal analysis of the signal, indicating that spectrum is not the only component of speech.…”
Section: Strategymentioning
confidence: 99%
“…Simulations with less than eight channels presented to normal-hearing listeners provide speech intelligibility scores in the same range as CI patients [ 1 ], [ 2 ]. Despite this good result, some researchers argue that the vocoded information does not offer the same sound quality as that of CIs and suggest the existence of perceptual and informational discrepancies between CI stimulation and performance-matched acoustical simulations [ 3 6 ]. Thus, a similar level of performance obtained for both real and simulated CI may hide different patterns of errors, limiting the validity of acoustic simulations through vocoders to evaluate new coding strategies.…”
Section: Introductionmentioning
confidence: 99%